P‐157: Narrow Border Black Photo Spacer Display Technology. Issue 1 (29th May 2019) - Zhang, Yihe; Zhang, Yinfeng; Cao, Wu; Li, Xuan; Zhang, Qi; Lin, Yunglun; Chiu, Chung-Yi; RAY,; Zhou, Hang
Abstract : In Black Photo Spacer (BPS) technology, Around gap mura (AGM) is the main reason which limits the application in narrow border display. Using gray tone mask design, AGM can be improved by reduing the film thickness and keeping cell gap uniformity. For the first time, we realize narrow border display application with BPS technology.